2012
DOI: 10.1128/aem.00474-12
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei Ferments the N -Acetylglucosamine Moiety of Fucosyl-α-1,3- N -Acetylglucosamine and Excretes l -Fucose

Abstract: ABSTRACTWe have previously characterized fromLactobacillus caseiBL23 three α-l-fucosidases, AlfA, AlfB, and AlfC, which hydrolyzein vitronatural fucosyl-oligosaccharides. In this work, we have shown thatL. caseiis able to grow in the presence of fucosyl-α-1,3-N-acetylg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…A previous work has shown that Lactobacillus casei BL23 is able to utilize the fucosyl-disaccharide fucosyl-␣1,3-N-acetylglucosamine (Fuc-␣1,3-GlcNAc), which is transported by a specific permease of the PTS class and split into L-fucose and N-acetylglucosamine by the ␣-L-fucosidase AlfB (29). However, this strain is not able to use L-fucose and only the N-acetylglucosamine moiety of Fuc-␣1,3-GlcNAc is catabolized, while L-fucose is quantitatively expelled to the growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…A previous work has shown that Lactobacillus casei BL23 is able to utilize the fucosyl-disaccharide fucosyl-␣1,3-N-acetylglucosamine (Fuc-␣1,3-GlcNAc), which is transported by a specific permease of the PTS class and split into L-fucose and N-acetylglucosamine by the ␣-L-fucosidase AlfB (29). However, this strain is not able to use L-fucose and only the N-acetylglucosamine moiety of Fuc-␣1,3-GlcNAc is catabolized, while L-fucose is quantitatively expelled to the growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…In the following years, the proteins forming the glucose-and mannose-specific PTSs in E. coli (202,203) and the lactose-specific PTS in S. aureus (204) were identified, and their role in transport and phosphorylation of the two hexoses and the disaccharide was established. Since then, a huge number of PTSs transporting a large variety of substrates, including hexoses, 6-deoxy-hexoses (14), amino sugars, N-acetyl-amino sugars, gluconic acids (205), pentitols (206,207), ascorbate (208), and disaccharides, have been identified. We recently obtained evidence that the E. faecalis maltose-specific EIICBA Mal (MalT) (15) also transports and phosphorylates the trisaccharide maltotriose and the tetrasaccharide maltotetraose (J. Deutscher, A. Hartke, J. Thompson, C. Magni, C. Henry, V. Blancato, G. Repizo, N. Sauvageot, A. Pikis, T. Kentache, and A. Mokhtari, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…In the last step, PϳEIIB transfers its phosphoryl group to a carbohydrate molecule bound to the cognate EIIC. There is so far only one carbohydrate, fucosyl-␣-1,3-N-acetylglucosamine, which is transported by a PTS (that of Lactobacillus casei) without being phosphorylated (14). All other carbohydrates are phosphorylated during their transport and subsequently converted into phosphorylated intermediates of either the Embden-MeyerhofParnas, pentose phosphate, or Entner-Doudoroff pathway.…”
mentioning
confidence: 99%
“…We have recently reported that probiotic bacterium L. casei strain BL23 can use Fuc-␣-1,3-GlcNAc as a carbon source and that AlfB is necessary for this. However, Fuc-␣-1,6-GlcNAc cannot be metabolized by L. casei (25). This suggests that, in spite of the high specific activity of AlfC on Fuc-␣-1,6-GlcNAc (13.6 mol fucose liberated/min · mg protein, compared to 27.5 mol fucose liberated from Fuc-␣-1,3-GlcNAc/min · mg protein for AlfB [7]), this disaccharide is not the natural substrate of AlfC.…”
mentioning
confidence: 99%